CULTURAL ISSUES IN TRANSLATION - J.Egamberdiyev; Jo'raboyeva Shohida (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: We know that every people, every nation has its own culture, traditions and identity. The word "culture" was used for the first time in the book "Primitive Culture" published in 1871 by the English scientist Edward B. Taylor. According to Taylor, culture includes knowledge, belief, law, tradition and various customs accepted by different members of society. Translation is not just the equivalent of a text, it is a difficult and complex process like rewriting the original.